Articulate storyline sebagai media dan sumber belajar siswa dalam pembelajaran jarak jauh - Ro’iyah, Maulidhotur (Maliki Interdisciplinary Journal, 2024)
Articulate storyline is a software application that functions as a support in learning. The application has a menu feature like Microsoft’s PowerPoint which is based on presentation points. This application makes learning projects more interesting by using a combination of moving animation features, backsounds and interactive images and videos. The purpose of this study was to determine the effectiveness, understanding and description of the Articulate storyline application. This study uses a descriptive qualitative approach which describes the results by observing and studying the literature on the Articulate storyline application. This application is suggested as a solution to challenges that occur in the world of education today, namely learning that can occur anytime and anywhere. So the Articulate Storyline application can be a learning support solution.